Proteomics Reveal the Effect of Exogenous Electrons on Electroactive Escherichia coli - Feng, Jiao; Feng, Jia; Li, Chunqiu; Xu, Sheng; Wang, Xin; Chen, Kequan (Frontiers in Microbiology, 2022)
Microbial cells utilizing electricity to produce high-value fuels and chemicals are the foundation of biocathodic bioelectrochemical system. However, molecular mechanisms of electron transfer and utilization have not been elucidated. In this work, Escherichia coli engineered by introducing the Mtr pathway from Shewanella oneidensis exhibited stronger electrochemical activity than control and could utilize exogenous electrons to stimulate metabolite profiles and boost succinate production in the bioelectrochemical system. Proteomic analysis and real-time PCR were performed to investigate the effect of exogenous electrons on electroactive E. coli. Bioinformatics analysis suggested that the proteins of molecular function associated with oxidoreductase activity,4 iron, 4 sulfur([4Fe-4S]) cluster binding, iron-sulfur cluster binding, and metal cluster binding were positively affected by exogenous electrons. Moreover, mapping to the Kyoto Encyclopedia of Genes and Genomes pathway database showed that the up-regulated proteins were mainly involved in metabolic pathways of tricarboxylic acid cycle, pyruvate metabolism and nitrogen metabolism pathway, providing support for the metabolic balance of microbial cells shifting toward reduced end-products due to electron utilization. Using a biochemical method, the ompF-overexpressed strain was employed to investigate the function of the channel protein. These findings provided a theoretical basis for further improving electron transfer and utilization efficiency, and contributed to the potential applications of bioelectrochemical system.